1992
DOI: 10.1152/jn.1992.68.5.1760
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic circuits sharpen tuning curves and modify response properties in the mustache bat inferior colliculus

Abstract: 1. The influence of bicuculline on the tuning curves of 65 neurons in the inferior colliculus of the mustache bat was investigated. Single units were recorded with multibarrel electrodes where one barrel contained bicuculline, an antagonist specific for gamma-amino-butyric acid (GABA)A receptors. Fifty-nine tuning curves were recorded from units that were sharply tuned to 60 kHz, the dominant frequency of the bat's orientation call, but six tuning curves were also recorded from units tuned to lower frequencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
136
1
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 218 publications
(157 citation statements)
references
References 0 publications
17
136
1
1
Order By: Relevance
“…A similar observation has been made in the IC of the bat (Covey et al, 1996). Pharmacological studies have shown that GABA or glycine blockers can broaden the frequency tuning of IC neurons, indicating that side band suppression is via inhibitory mechanisms (Vater et al, 1992;Yang et al, 1992). Interaural delay curves generated from the response to the binaural-beat stimulus (for details, see Yin and Kuwada, 1983;Kuwada et al, 1987).…”
Section: Complexity Of Monaural and Binaural Responsessupporting
confidence: 56%
“…A similar observation has been made in the IC of the bat (Covey et al, 1996). Pharmacological studies have shown that GABA or glycine blockers can broaden the frequency tuning of IC neurons, indicating that side band suppression is via inhibitory mechanisms (Vater et al, 1992;Yang et al, 1992). Interaural delay curves generated from the response to the binaural-beat stimulus (for details, see Yin and Kuwada, 1983;Kuwada et al, 1987).…”
Section: Complexity Of Monaural and Binaural Responsessupporting
confidence: 56%
“…One explanation for this difference in the effects of inhibition on direction selectivity and inseparability is that blocking inhibition frequently causes an expansion of the excitatory receptive field, in which the expansion is not uniform along the spectrotemporal axis (Yang et al, 1992;Palombi and Caspary, 1996;LeBeau et al, 2001;Klug et al, 2002). Such a nonuniform expan- 6.…”
Section: Inhibition Shapes Directional Selectivitymentioning
confidence: 99%
“…Thus, the physiological response to increasing sound level also involves inhibition of the activity of narrow-band, low intensity-sensitive neurones. Such inhibition is in evidence from the dorsal cochlear nucleus all the way up to the cortex and there are certainly local inhibitory contributions to non-monotonicity at least as high as the inferior colliculus (Yang et al, 1992). At the cortical level, there are profuse local inhibitory influences (Cox et al,.…”
Section: A Neurophysiological Bases For the Auditory Activation Chanmentioning
confidence: 99%